Pengaruh Penggunaan Media Pembelajaran Augmented Reality (AR) Terhadap Hasil Belajar IPA Siswa Kelas V di SDIT Qurrata Aini Baitussalam - shofiatul mustafidah; Muhammad Fahri; Abrista Devi (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2025)
This study aims to determine the effect of using Augmented Reality (AR) learning media on the science learning outcomes of fifth-grade students at SDIT Qurrata Aini Baitussalam. The method used is an experiment comparing a control class and an experimental class. The results show that students in the experimental class who used AR learning media achieved higher test scores compared to students in the control class. Statistical testing using the Independent Samples T-Test was conducted to examine the significance of the differences in learning outcomes between the two classes. Prior to hypothesis testing, the Kolmogorov-Smirnov normality test confirmed that the data were normally distributed, meeting the assumptions for parametric testing. The test results showed a significant t-value (- 10.123) with a p-value of 0.000 (p < 0.05). The p-value, which is well below the significance level of 0.05, and the absolute t-value exceeding the t-table value (approximately 3.623) indicate a significant difference between the average science learning outcomes in both classes. Therefore, it can be concluded that the use of Augmented Reality learning media has a positive effect on the science learning outcomes of students.